Immanuel Kant: Groundwork of the Metaphysics of Morals : c - Kant, Immanuel; Gregor, Mary; Timmermann, Jens (Cambridge : Cambridge University Press, 2011)
Published in 1785, the Groundwork of the Metaphysics of Morals is one of the most powerful texts in the history of ethical thought. In this book, Immanuel Kant formulates and justifies a supreme principle of morality that issues universal and unconditional moral commands. These commands receive their normative force from the fact that rational agents autonomously impose the moral law upon themselves. As such, they are laws of freedom. This volume contains the first facing-page German-English edition of Kant's Groundwork. It presents an authentic edition of the German text and a carefully revised version of Mary Gregor's acclaimed English translation, as well as editorial notes and a full bilingual index. It will be the edition of choice for any student or scholar who is not content with reading this central contribution to modern moral philosophy through the veil of English translation.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).